Parallel distributed system for social networks streaming data analysis - Doroshenko, А.Yu.; Titov, D.S. (Інститут програмних систем НАН України, 2017)
A comparison of the effectiveness of remote procedure call technology (RMI) and the framework for distributed computing (Hazelcast), as a means for the development of the cluster system, is performed. The parallel distributed dynamically scalable faulttolerant system for processing large amount of streaming data is proposed. The inspection and initial study of this system on the example of data from the Twitter social network is performed. The mechanism of the deployment of the created cluster to the cloud platform is examined.